Pengaruh Kualitas Pelayanan Pengiriman Barang Suku Cadang Motor dan Harga yang Mempengaruhi Kepuasan Pelanggan dan Implikasinya terhadap Loyalitas Pelanggan: Kasus PT. Alpindo Mitra Baja Sukabumi - Qubaila Fazrin Ega Soraya (LP2M CBI PRESS, 2019)
This study aims to determine the effect of Motorcycle Parts Delivery Service Quality and Price on Customer Satisfaction and Customer Loyalty (Case Study on PT. Alpindo Mitra Baja Sukabumi). Both primary and secondary data were gathered. Secondary data were gathered from various sources such as journals, books, and other related publications. Primary data were gathered using questionnaire that were distributed to the respondents. This research design is using causal relationships.Research population is 110 customers of PT. Alpindo Mitra Baja Sukabumi. By using Slovin formula and a simple randomsampling technique, a total sample of 87 respondents were acquired. The Research Result is that the delivery service qualityvariable and the price variable are very influential on customer satisfaction and customer loyalty. This research result suggests PT. Alpindo Mitra Baja Sukabumi to focus on delivery service quality and price especially the pricing reasonable and timely delivery to create better customer loyalty.